L’action créatrice par rapport à la Métaphysique de Thomas d’Aquin - Fernando Martin De Blassi (Medievalista)
This work deals with the creative action in relation to being (esse) and other aspects of the metaphysics of Thomas Aquinas. The author refers directly to the sources with a hermeneutics support of specialized literature. He attempts to capture the synthesis achieved by Thomas Aquinas about the divine essence as an active and creative power, to show that all the perfections dispersed in created beings pre-exist in it, since all that is, and that all perfection, are only ways of being, different forms of participation in being (esse), which are caused by one who is in essence.